Determinants of Healthy Rice Seed and Crop Management Adoption among Rice Farmers in Bogor Regency - Feldy Khalid; Anna Fatchiya; Dyah Retna Puspita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aimed to analyze the adoption level of Healthy Rice Seed and Crop Management (HRSCM) and examine determinants influencing its adoption among rice farmers in Bogor Regency, Indonesia. The study was conducted in Jonggol and Tanjungsari Districts, involving 105 rice farmers who participated in the Integrated Crop Management Farmer Field School (ICM-FFS) program. Data were collected through structured questionnaires and analyzed using descriptive statistics and Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that the overall HRSCM adoption level was generally high. SEM-PLS analysis revealed that environmental support had the strongest positive effect on HRSCM adoption (? = 0.669; p<0.001), followed by farmer characteristics (? = 0.232; p<0.001) and FFS extension effectiveness (? = 0.156; p<0.05). Extension support showed a significant negative effect (? = ?0.304; p<0.001), whereas farmers’ perceptions of innovation characteristics had no significant effect on adoption behavior. These findings suggest that once farmers are familiar with HRSCM practices, adoption decisions are shaped primarily by environmental and institutional conditions rather than by differences in farmers’ perceptions of innovation characteristics. Improving access to production resources, strengthening institutional and environmental support, and developing adaptive extension systems are therefore essential for increasing HRSCM adoption. Contribution to Sustainable Development Goals (SDGs):SDG 1: No Poverty SDG 2: Zero Hunger